Circulating Vitamin D Levels and Risk of Vitiligo: Evidence From Meta-Analysis and Two-Sample Mendelian Randomization - Song, Jie; Liu, Ke; Chen, Weiwei; Liu, Bin; Yang, Hong; Lv, Linshuoshuo; Sun, Xiaohui; Mao, Yingying; Ye, Ding (Frontiers in Nutrition, 2021)
Background: The association between circulating vitamin D levels and risk of vitiligo was inconsistent among observational studies, and whether these observed associations were causal remained unclear. Therefore, we aimed to evaluate the effect of vitamin D on the risk of vitiigo using meta-analysis and Mendelian randomization (MR). Methods: At the meta-analysis stage, literature search was performed in PubMed and Web of Science to identify eligible observational studies examining the association of circulating 25-hydroxyvitamin D [25(OH)D] or 25-hydroxyvitamin D3 [25(OH)D3] levels with risk of vitiligo up to April 30, 2021. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) of 25(OH)D and 25(OH)D3 in patients with vitiligo relative to controls were pooled. Then at the MR stage, genetic instruments for circulating 25(OH)D (N = 120,618) and 25(OH)D3 (N = 40,562) levels were selected from a meta-analysis of genome-wide association studies (GWAS) of European descent, and summary statistics of vitiligo were obtained from a meta-analysis of three GWASs including 4,680 cases and 39,586 controls. We used inverse-variance weighted (IVW) as main method, followed by weighted-median and likelihood-based methods. Pleiotropic and outlier variants were assessed by MR-Egger regression and MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test. Results: In the meta-analysis, patients with vitiligo had a lower level of circulating 25(OH)D compared with controls [SMD = −1.40; 95% confidence interval (CI): −1.91, −0.89; P < 0.001], while no statistically significant difference of 25(OH)D3 between vitiligo cases and controls was found (SMD = −0.63; 95% CI: −1.29, 0.04; P = 0.064). However, in the MR analyses, genetically predicted 25(OH)D [odds ratio (OR) = 0.93, 95% CI = 0.66–1.31, P = 0.66] and 25(OH)D3 levels (OR = 0.95, 95% CI = 0.80–1.14, P = 0.60) had null associations with risk of vitiligo using the IVW method. Sensitivity analyses using alternative MR methods and instrumental variables (IV) sets obtained consistent results, and no evidence of pleiotropy or outliers was observed. Conclusion: Our study provided no convincing evidence for a causal effect of 25(OH)D or 25(OH)D3 levels on the risk of vitiligo. Further longitudinal and experimental studies, as well as functional studies are warranted to elucidate the role of vitamin D in the development of vitiligo.